A review of nosocomial infection among postoperative patients admitted at Cebu Doctors Hospital pediatric ward - Chiu, Vivina; Aguirre, Lerma G.
Vesicoureteral reflux is defined as the abnormal backflow of urine from the bladder into the ureter or into the ureter and kidney. It is the most common abnormality found in children with UTI and has been reported in 30-50% of affected children whether or not the infection is symptomatic or asymptomatic. With the high percentage of vesicoureteral reflux (VUR) in Pediatric patients with UTI, this study aims to enlighten Pediatricians on the importance of a radiologic evaluation on patients 14 years old and below with Urinary Tract Infection (UTI) who had undergone a voiding cystourenthrogram (VCUG). 15 (32%) showed VUR, 8 of whom were males while 7 were females with no statistically significant difference between the 2 sexes. Grade I was the most common type of reflux. The most severe types of reflux were seen in children below the age of 6 years old with preponderance in male infants. 11 patients had unilateral involvement while 4 had bilateral involvement. Patients with UTI documented by urine culture should at least have a radiologic evaluation after their first infection with particular emphasis in younger patients.
Cebu Doctors' Proceedings, 1993 9 (1) pages 69-75
Keywords: Cross Infection